Recommendations for benefit–risk assessment methodologies and visual representations§. Issue 3 (22nd January 2016) - Hughes, Diana; Waddingham, Ed; Mt‐Isa, Shahrul; Goginsky, Alesia; Chan, Edmond; Downey, Gerald F.; Hallgreen, Christine E.; Hockley, Kimberley S.; Juhaeri, Juhaeri; Lieftucht, Alfons; Metcalf, Marilyn A.; Noel, Rebecca A.; et al.
Abstract: Purpose: The purpose of this study is to draw on the practical experience from the PROTECT BR case studies and make recommendations regarding the application of a number of methodologies and visual representations for benefit–risk assessment. Methods: Eight case studies based on the benefit–risk balance of real medicines were used to test various methodologies that had been identified from the literature as having potential applications in benefit–risk assessment. Recommendations were drawn up based on the results of the case studies. Results: A general pathway through the case studies was evident, with various classes of methodologies having roles to play at different stages. Descriptive and quantitative frameworks were widely used throughout to structure problems, with other methods such as metrics, estimation techniques and elicitation techniques providing ways to incorporate technical or numerical data from various sources. Similarly, tree diagrams and effects tables were universally adopted, with other visualisations available to suit specific methodologies or tasks as required. Every assessment was found to follow five broad stages: (i) Planning, (ii) Evidence gathering and data preparation, (iii) Analysis, (iv) Exploration and (v) Conclusion and dissemination. Conclusions: Adopting formal, structured approaches to benefit–risk assessment was feasible in real‐world problems and facilitated clear, transparent decision‐making. Prior to this work, no extensive practical application and appraisal of methodologies had been conducted using real‐world case examples, leaving users with limited knowledge of their usefulness in the real world. The practical guidance provided here takes us one step closer to a harmonised approach to benefit–risk assessment from multiple perspectives. Copyright © 2016 John Wiley & Sons, Ltd.